Recent advances of electrochemical and optical enzyme-free glucose sensors operating at physiological conditions - Adeel, Muhammad; Rahman, Md. Mahbubur; Caligiuri, Isabella; Canzonieri, Vincenzo; Rizzolio, Flavio; Daniele, Salvatore (Biosensors & bioelectronics, 2020)
Diabetes is a pathological condition that requires the continuous monitoring of glucose level in the blood. Its control has been tremendously improved by the application of point-of-care devices. Conventional enzyme-based sensors with electrochemical and optical transduction systems can successfully measure the glucose concentration in human blood, but they suffer from the low stability of the enzyme. Non-enzymatic wearable electrochemical and optical sensors, with low-cost, high stability, point-of-care testing and online monitoring of glucose levels in biological fluids, have recently been developed and can help to manage and control diabetes worldwide. Advances in nanoscience and nanotechnology have enabled the development of novel nanomaterials that can be implemented for the use in enzyme-free systems to detect glucose. This review summarizes recent developments of enzyme-free electrochemical and optical glucose sensors, as well as their respective wearable and commercially available devices, capable of detecting glucose at physiological pH conditions without the need to pretreat the biological fluids. Additionally, the evolution of electrochemical glucose sensor technology and a couple of widely used optical detection systems along with the glucose detection mechanism is also discussed. Finally, this review addresses limitations and challenges of current non-enzymatic electrochemical, optical, and wearable glucose sensor technologies and highlights opportunities for future research directions. •Recent advances of enzyme-less glucose sensors at physiological pH are reviewed.•Fundamentals of electrochemical and optical glucose sensors are described.•Advances in the development of nanomaterials and molecular recognition elements are discussed.•Wearable glucose sensors for continuous glucose monitoring are reviewed.•The perspective of electrochemical, optical, and wearable glucose sensors is envisioned.